PENGARUH MENGUNYAH PERMEN KARET RENDAH GULA TERHADAP INTERDIALYTIC WEIGHT GAIN (IDWG) PADA PASIEN GAGAL GINJAL KRONIK (GGK) DENGAN HEMODIALISIS YANG DIRAWAT DI RSUD ARIFIN ACHMAD PROVINSI RIAU - Henni Afriani; Bayhakki Bayhakki; Yulia Irvani Dewi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Chronic Kidney Disease (CKD) is a progressive and irreversible kidney damage that causes impaired function of kidney in removing toxic and metabolic waste products characterized by the presence of protein in the urine. This research aimed to determine the effect of chewing low-sugar gum on Interdialytic Weight Gain (IDWG). This research method used Quasy Experiment with non-equivalent control group design divided into experiment group and control group. The research was conducted in Arifin Achmad General Hospital Riau Province to 32 respondents taken using purposive sampling technique divided into 16 respondents for the control group and 16 respondents for experimental group. The instrument using scale. The analysis used univariate analysis to see frequency and bivariate with Independent sample t test and Dependent sample t test. The results showed that the average IDWG experimental group before chewing low-sugar gum was 2.4 kg. While IDWG after chewing gum low sugar was 1.9. The result of bivariate test showed p value = 0.005 <α (0.05) which meant there was difference IDWG after given intervention. It is expected to nurse can provide non-pharmacological therapy like chewing low-sugar gums to manage the body fluid of patient with CKD.Key words : Chewing gum , Chronic Kidney Disease, IDWG